Domestic violence and the role of the dentist from the public health perspective: a review of scientific literature - Ferraz e Silva, Fernanda; Pereira Franco de Sá, Ronice Maria; Paranhos, Luiz Renato (Acta Bioethica, 2014)
This study systematically reviewed the systematic production about domestic violence, based on the professional practice of the dentist in a multidisciplinary and interdisciplinary context, from the perspective of public health. The goal was to verify how this issue has been addressed, identify which is the most explored focus, and point out possible gaps. The search was conducted in the Virtual Health Library (BVS Brazil), by selecting 40 articles: 37 on Lilacs, 2 in BBO and only 1 in SciELO, from 2000 to 2011. Of the total scientific production analyzed, 20% references have cited the dentist along the paper, among these 50% pointed for the practice of the dentist in a multidisciplinary and interdisciplinary context, from the perspective of public health. The health professional role in a multidisciplinary and interdisciplinary context, from the perspective of public health corresponded to 72.5% studies. In this way, the need for studies on the performance of professional dentist in interdisciplinary and multidisciplinary team is necessary before the Brazilian context, being an open and wide field to be explored, from the perspective of public health.